IDENTIFIKASI PENGELOLAAN WAKAF PRODUKTIF PADA PIMPINAN DAERAH MUHAMMADIYAH LUMAJANG - Hilda Gita Mayasari; A. Syifa'ul Qulub (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to describe management of productive endowments managed by the Regional Leadership Muhammadiyah Lumajang where in this case a nazhir appointed by the United Muhammadiyah to manage the productive endowments. This research uses descriptive qualitative approach by using case study strategy. Analytical techniques based on theoretical prepositions follow theoretical prepositions that guide case studies. Data validity technique using triangulation technique, that is test the credibility of data that have been obtained by correcting through some technique, like interview, observation, and documentations. The results show that Muhammadiyah Regional Leaders have managed their assets or productively in order to achieve the benefit of Moeslims in Lumajang District. Endowments management conducted by PDM Lumajang is divided into four business charities, namely religion, education, health, social and economic. In the management of productive endowments PDM Lumajang can do several things, namely to perform management functions in the implementation of productive endowments and create jobs for local communities.Keywords: Productive Endowments, Muhammadiyah, Economic IndependenceREFFERENCESAl Bujairomi, Sulaikman bin Muhammad. 2015. Bujairomi ,,alaa al khatib. Offline. Maktabah Syamilah. Al Hasani, Muhammad Ar Rouf Qosimiy. 2007. At Tathwiir At Takhrijiy wa At Tasyri’i li An Nidzomi Al-Waqfi: Numudzujil Iqtishodi At Tazommuniy. Jordan: Chasier du CREAD.Bamualim, Chaider S dan Irfan Abubakar, 2005. Revitalisasi Filantropi Islam, Studi Kasus Lembaga Zakat dan Wakaf di Indonesia. Pusat Bahasa dan Budaya UIN Syarif Hidayatullah.Bungin, M. B. 2007. Penelitian Kualitatif. Jakarta: KencanaDjunaidi, Achmad. 2006. Menuju Era Wakaf Produktif. Jakarta: Mitra Abadi Press.Hafidhuddin, Didin. 2007. Agar Harta Berkah dan Bertambah: Gerakan Membudayakan Zakat, Infak, Sedekah, dan Wakaf. Jakarta: Gema Insani Press.Hasan, Sudirman. 2011. Wakaf Uang: Perspektif Fikih, Hukum Positif, dan Manajemen. Malang: UIN Maliki Press (Anggota IKAPI).Hashmi, Sherafat Ali. 1987. Management of Waqf: Past and Present, dalam Proceeding of The Seminar: Management and Development of Awqaf Properties. Jeddah: Islamic Research and Training Institute, Islamic Development Bank.Lubis, Suhrawardi K dkk. 2010. Wakaf dan Pemberdayaan Umat. Jakarta: Sinar Grafika.Kotler, Philip dan Gary Amstrong. 2007. Dasar-Dasar Pemasaran Edisi Kesembilan Jilid I. Jakarta: PT. Indeks. M. Manullang. Dasar-Dasar Manajemen. Yogyakarta: Universitas Gadjah Mada.Mizan, Fitra. 2008. Efektivitas Tabungan Wakaf Indonesia dalam Penghimpunan dan Pendayagunaan Wakaf. Skripsi Tidak Diterbitkan. Jakarta UIN.Muhammad Abid Abdullah Al-Kabisi. 2004. Hukum Wakaf. Jakarta: IIMAN.Muljawan, Dadang, dkk. 2016. Wakaf: Pengaturan dan Tata Kelola yang Efektif. Jakarta: Bank Indonesia.Mulyani. 2013. Pengelolaan Wakaf Produktif di Yayasan Perguruan Tinggi Nahdlatul Ulama’ Surakarta. Skripsi Jurusan Syariah Program Studi Ahwal Al-Syakhsyiyyah Sekolah Tinggi Agama Islam Negeri (STAIN) Surakarta.Nasution, M.N. 2005. Manajemen Mutu Terpadu (Total Quality Management). Ghalia Indonesia, Bogor.Nazir, Moh. 2003. Metode Penelitian. Ghalia Indonesia.Pimpinan Pusat Muhammadiyah. 2005. Anggaran Dasar dan Anggaran Rumah Tangga Muhammadiyah. YogyakartaQahaf, Mundzir. 2005. Manajemen Wakaf Produktif. Jakarta: Khalifa.Rozalinda. 2015. Manajemen Wakaf Produktif. Jakarta: PT Rajagrafindo Persada.Sabiq, Saddiq. 1987. Fikih Sunnah 14. Bandung: PT Alma’arif.Sugiyono. 2015. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Wibisono, Yusuf (ed). 2011. Paradigma Baru Pengelolaan Wakaf Untuk Kesejahteraan Bangsa dalam Indonesia Shari’ah Economic Outlook 2011. Jakarta: Lembaga Penerbit FEUI.Yin, Robert K. 2013. Studi Kasus: Desain dan Metode. Jakarta: PT. Raja Grafindo Persada.